An evaluation of an English Language immersion programme for ESL preservice teachers - Hudson, Peter; Hudson, Sue (Penerbit UKM, 2003)
A six-week English Language Immersion Programme (ELIP) was conducted for 19 Hong Kong preservice ESL teachers at an Australian regional university. This programme focused on enhancing the students’ English knowledge and skills, as well as providing pedagogical knowledge for teaching English as a Second Language (ESL) in the primary school context. Predominantly a quantitative study, two surveys, a pretest and posttest, were administered to determined confidence levels on English language proficiency. These results, and standardised test results, indicated that short-term English immersion programmes could develop English language proficiency and substantially enhance ESL teaching confidence. It concluded that valid and reliable assessments need to be continually developed as these can aid towards providing trustworthy accountability, certifiable accreditation, and a way to improve upon immersion programmes and practices.